Roles of Reactive Oxygen Species in Cardiac Differentiation, Reprogramming, and Regenerative Therapies - Liang, Jialiang (Oxid Med Cell Longev, 2020)
Reactive oxygen species (ROS) have been implicated in mechanisms of heart development and regenerative therapies such as the use of pluripotent stem cells. The roles of ROS mediating cell fate are dependent on the intensity of stimuli, cellular context, and metabolic status. ROS mainly act through several targets (such as kinases and transcription factors) and have diverse roles in different stages of cardiac differentiation, proliferation, and maturation. Therefore, further detailed investigation and characterization of redox signaling will help the understanding of the molecular mechanisms of ROS during different cellular processes and enable the design of targeted strategies to foster cardiac regeneration and functional recovery. In this review, we focus on the roles of ROS in cardiac differentiation as well as transdifferentiation (direct reprogramming). The potential mechanisms are discussed in regard to ROS generation pathways and regulation of downstream targets. Further methodological optimization is required for translational research in order to robustly enhance the generation efficiency of cardiac myocytes through metabolic modulations. Additionally, we highlight the deleterious effect of the host's ROS on graft (donor) cells in a paracrine manner during stem cell-based implantation. This knowledge is important for the development of antioxidant strategies to enhance cell survival and engraftment of tissue engineering-based technologies. Thus, proper timing and level of ROS generation after a myocardial injury need to be tailored to ensure the maximal efficacy of regenerative therapies and avoid undesired damage.